Efektivitas model pembelajaran kooperatif tipe stad dalam upaya meningkatkan motivasi dan prestasi belajar matematika siswa kelas XI IPA SMA Negeri 3 Bantul tahun pembelajaran 2013/2014 - Christina Sri Purwanti (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2015)
This study aims to find out how in implementing STAD type cooperative learning model to increase student’s motivation and Mathematics learning achievement, its strengths, and weaknesses, as well as its effectiveness when implemented in XI Science class at SMAN 3 Bantul academic year 2013/2014. This was a classroom action research which was followed by an effectiveness test. The classroom action research was conducted in two cycles, where each includes planning, implementation, observation, and reflection. The effectiveness test was conducted by using Kirkpatrick’s evaluation model with four levels of evaluation, namely reaction, learning, behavior and results evaluations. The instrument used were questionnaires and tests and the data collection techniques were questionnaires, tests, observations, and in-depth interviews. The quantitative data were analyzed the mean scores of the questionnaires, the achievement data was analyzed the completeness percentage derived from the tests, while the qualitative data was analyzed using the classification, narratives, comparisons and causality techniques. The results of the research showed that applying STAD type cooperative learning model could increase class XI Science students’ motivation and achievement of Mathematics learning at SMAN 3 Bantul academic year 2013/2014. STAD type cooperative learning model implemented among the students of XI Science class at SMAN 3 Bantul academic year 2013/2014 included classroom presentation, group study, and quizzes. STAD type of cooperative learning model also showed advantages. Students could complement one another and understood the material better, and the more important, they would have to do prior preparations before classes.  Additionally, they also felt happy and continuous interests. Yet, it also posed some disadvantages like less varied sample exercises, the need for more time, student’s lacks of confidence and student’s difficult to focus. STAD type cooperative learning model was proven to be effective in improving student’s motivation and achievement.